Absorption–desorption of carbon dioxide in carbon honeycombs at elevated temperatures - Krainyukova, N.V.; Bogdanov, Y.; Kuchta, B. (Физика низких температур, 2019)
The recently synthesized honeycomb carbon allotrope has numerous potential applications, in particular for storage of gases inside carbon matrices. In this work this carbon form was experimentally studied in its denser form in order to estimate the upper temperature limit for keeping a gas inside the cellular structure. Along with the previously reported random honeycombs of a zigzag type we have also revealed the densest armchair structure. The mechanism of absorption–desorption of carbon dioxide studied by means of high energy electron diffraction at low temperatures showed the two — stage character of the observed desorption at elevated temperatures. This effect is associated to the weaker or stronger bonding of molecules with pore walls depending on the specific configuration of channels with different sizes. We have found that complete desorption of CO₂ does not occur even at the temperatures about three times higher as compared with the sublimation point of carbon dioxide in our vacuum conditions.